Implementation of Artificial Intelligence&Machine Learning for Sustainable Medical Devices (International Journal of Food and Nutritional Sciences, 2023)
Artificial intelligence (AI) has been developing rapidly in recent years in terms of softwarealgorithms, hardware implementation, and applications in a vast number of areas. In this review,we summarize the latest developments of applications of AI in biomedicine, including diseasediagnostics, living assistance, biomedical information processing, and biomedical research.